A Review of Risk Factors for Methamphetamine-Related Psychiatric Symptoms - Chang, Xiangwen; Sun, Yan; Zhang, Yang; Muhai, Jiana; Lu, Lin; Shi, Jie (Frontiers in Psychiatry, 2018)
Abstract The illegal use of methamphetamine (MA) is a growing public health concern globally, causing a series of adverse reactions. The prominent negative effect of MA use is MA-related psychiatric symptoms (MAP) which is much higher than the general population. MAP often includes multiple dimensions of cognitive impairment and induces adverse consequences such as violence and suicide. Therefore, it is necessary to examine the factors that affect the development of psychosis in those who use MA. Besides, the evaluate assessment methods of MAP are generally disunity. Therefore, here we compare the different features of MAP and various kinds of the assessment instruments, and summarized the risk factors of MAP from MA use-related factors, sociodemographic variables and life events and genetic factors. We found that the association between MA-related risk factors and MAP were greatly consistent. The likelihood of experiencing MAP was significantly associated with a larger or higher frequency of MA dose and other MA-related factors among MA users. However, the reports about other MAP–related risk factors (e.g, life events and genetics) were relatively inconsistent. The causal and longitudinal studies which focus on multilateral comparison would be desired in the future. This review would provide high quality evidence on risk factors of MAP, which would be helpful for developing early prevention and treatment method of MAP. Keywords: Methamphetamine (MA), methamphetamine-related psychiatric symptoms (MAP), assessment instruments, risk factors, methamphetamine use related factors, sociodemographic variables and life events, genetic factors.